2011
DOI: 10.1007/s10886-011-9975-7
|View full text |Cite
|
Sign up to set email alerts
|

Elevated Carbon Dioxide and/or Ozone Concentrations Induce Hormonal Changes in Pinus tabulaeformis

Abstract: We investigated endogenous plant hormones and needle growth in Pinus tabulaeformis plants grown in open-top chambers and exposed to ambient or elevated concentrations of carbon dioxide (CO(2)) and/or ozone (O(3)). Exposure to elevated CO(2) for 100 days significantly increased the change in fresh needle weight, indole-3-acetic acid (IAA), isopentenyl-adenosine (iPA), and dihydrozeatin riboside (DHZR) content. Abscisic acid (ABA) content decreased, and no effect was observed on zeatin riboside (ZR) content or c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 36 publications
(42 reference statements)
1
5
1
Order By: Relevance
“…Our study also showed that elevated CO 2 did not offset the negative effects of elevated O 3 on the plant growth. This finding is in contrast to other studies in which elevated CO 2 has been shown to ameliorate the negative effects of elevated O 3 47 , 48 . These contradictory results may be due to the interactions between CO 2 and O 3 depending on plant species 49 and plant developmental stages 17 .…”
Section: Discussioncontrasting
confidence: 99%
“…Our study also showed that elevated CO 2 did not offset the negative effects of elevated O 3 on the plant growth. This finding is in contrast to other studies in which elevated CO 2 has been shown to ameliorate the negative effects of elevated O 3 47 , 48 . These contradictory results may be due to the interactions between CO 2 and O 3 depending on plant species 49 and plant developmental stages 17 .…”
Section: Discussioncontrasting
confidence: 99%
“…The role of hormone pathways in regulating the growth and metabolic responses to elevated CO 2 is not well known, despite there being a few reports (e.g., Li et al, 2011 ; Ribeiro et al, 2012 ; Zavala et al, 2013 ). Elevated CO 2 can promote an accumulation in the salicylic acid (SA, Zavala et al, 2013 ) and brassinosteroids (BR; Jiang et al, 2012 ), while reducing Jasmonates (JA) and ethylene concentrations ( Zavala et al, 2013 ; Vaughan et al, 2014 ).…”
Section: Responses Of Critical Biological Processes To Elevated Co mentioning
confidence: 99%
“…In one recent report, BRs were found to enhance the stimulation of plant growth and photosynthetic potential under elevated CO 2 ( Jiang et al, 2012 ). An increase in the indole-3-acetic acid (IAA), isopentenyl-adenosine (iPA), and dihydrozeatin riboside (DHZR) was found, while a decrease in the ABA and unchangeable zeatin riboside (ZR) occurred in Pinus tabulaeformis plants exposed to elevated CO 2 , which can encounter O 3 exposure effects to alleviate damage ( Li et al, 2011 ). The iPA, DHZR, and ZR are recognized as the most commonly active cytokinins (CTKs) in plants.…”
Section: Responses Of Critical Biological Processes To Elevated Co mentioning
confidence: 99%
“…Previous studies have shown that because of strong oxidative stress, pre-exposure to O 3 can prime tomato leaves for an enhanced defense against subsequent herbivorous insect infestation by upregulating the expression of salicylic acid (SA)-dependent defensive gene pathogenesis-related protein and increasing the emission of jasmonic acid (JA)-mediated monoterpene volatiles by tomato plants to decrease the population abundance and feeding fitness of B. tabaci (Cui et al, 2012;Cui et al, 2014). In addition to the SA and JA signaling pathways, O 3 pre-exposure activates the abscisic acid (ABA) signaling pathway, with a significant increase in ABA accumulation via the direct oxidation of the ABA precursor xanthoxin and the expression of ABA-related genes in some species, such as Arabidopsis, tomato, and Chinese pine (Li et al, 2011;McAdam et al, 2017). ABA is an important signal in regulating phloem-sucking insect infestation (Kerchev et al, 2013;Hillwig et al, 2016).…”
Section: Introductionmentioning
confidence: 99%